Modelling of pyroelectric response in inhomogeneous ferroelectric-semiconductor films - Morozovska, A.N.; Eliseev, E.A.; Remiens, D.; Soyer, C. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
We have modified the Landau-Khalatnikov approach and shown that the pyroelectric response of inhomogeneous ferroelectric-semiconductor films can be described using six coupled equations for six order parameters: average displacement, its mean-square fluctuation and correlation with charge defect density fluctuations, average pyroelectric coefficient, its fluctuation and correlation with charge defect density fluctuations. Coupled equations demonstrate the inhomogeneous reversal of pyroelectric response in contrast to the equations of the Landau-Khalatnikov type, which describe the homogeneous reversal with the sharp pyroelectric coefficient peak near the thermodynamic coercive field value. Within the framework of our model, the pyroelectric hysteresis loop becomes much smoother, thinner and lower as well as the pyroelectric coefficient peaks near the coercive field completely disappear with increase in disordering caused by defects. This effect is similar to the well-known "square to slim transition" of the ferroelectric hysteresis loops in relaxor ferroelectrics. Also the increase of defect concentration leads to the drastic decrease of the coercive field typical for disordered ferroelectrics. Usually pyroelectric hysteresis loops of doped and inhomogeneous ferroelectrics have typical smooth shape without any pyroelectric coefficient peaks, and the coercive field values much lower than the thermodynamic one. Therefore, our approach qualitatively explains available experimental results. A rather well quantitative agreement between our modelling and typical Pb(Zr,Ti)O₃ film pyroelectric and ferroelectric loops has been obtained.